The effects of geometric non-additivity on the wetting of symmetric mixtures at a wall. (14th December 2017) - Patrykiejew, A
Abstract: The paper discusses the behavior of symmetric binary mixtures of Lennard-Jones particles in contact with non-selective smooth walls. Using the Monte Carlo simulation method in the grand canonical ensemble, we have elucidated the effects of negative and positive geometric non-additivity on the wetting behavior in a series of systems characterized by different strength of the fluid-wall interaction. It has been shown that even in the case of mixtures which do not exhibit demixing transition the geometric non-additivity considerably changes the wetting behavior of symmetric mixtures. In particular, it has been demonstrated that the structure and stability of the bulk solid and liquid phases play an important role, and lead to non-monotonous changes of the wetting temperature when the geometric non-additivity changes. It has been also shown that the systems with negative geometric non-additivity exhibit a triple-point wetting over a certain range of the surface potential strength. In such cases, the first-order wetting transition occurs when the wetting temperature is higher than the bulk triple point temperature and becomes a continuous transition (critical wetting) when the triple wetting occurs. On the other hand, the systems with positive geometric non-additivity have not been observed to show the triple point wetting, and the wetting temperature decreases smoothly when the strength of the surface field increases. For sufficiently strong surface fields, the adsorbed film develops in a layer-by-layer mode, independently of the geometric non-additivity.